Structure-based design of inhibitors of coagulation factor XIa with novel P1 moieties. Issue 7 (1st April 2015) - Pinto, Donald J.P.; Smallheer, Joanne M.; Corte, James R.; Austin, Erin J.D.; Wang, Cailan; Fang, Tianan; Smith, Leon M.; Rossi, Karen A.; Rendina, Alan R.; Bozarth, Jeffrey M.; Zhang, Ge; Wei, Anzhi; et al.
Graphical abstract: Abstract: Compound2 was previously identified as a potent inhibitor of factor XIa lacking oral bioavailability. A structure-based approach was used to design analogs of2 with novel P1 moieties with good selectivity profiles and oral bioavailability. Further optimization of the P1 group led to the identification of a 4-chlorophenyltetrazole P1 analog, which when combined with further modifications to the linker and P2′ group provided compound32 with FXIa K i  = 6.7 nM and modest oral exposure in dogs.